Borderline exegesis - Vaage, Leif E. (Signifying (on) Scriptures., 2014)
"A textual interpretation of the book of Job, the Gospel of Matthew, the Epistle of James, and Revelation. Includes analysis of the utopian imagination at work in a borderline exegesis"--Provided by publisher